Effect of Trust, Privacy, Service Quality and Customer Satisfaction on the Success of Electronic Customer Relationship Management (E-CRM) Systems in Nepalese Insurance Sector - Bhattarai, Yunish (Nepalese Journal of Management, 2025)
This study examines the effect of trust, privacy, service quality, and customer satisfaction on the success of electronic customer relationship management (E-CRM) systems in Nepalese insurance sectors. Success of electronic customer relationship management is the dependent variable. The selected independent variables are privacy, reliability, responsiveness, trust, and customer satisfaction. The primary source of data is used to assess the opinions of respondents regarding privacy, reliability, responsiveness, trust, customer satisfaction, and success of electronic customer relationship management. The study is based on primary data of 131 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the effect of trust, privacy, service quality, and customer satisfaction on the success of electronic customer relationship management (E-CRM) systems in Nepalese insurance sectors. The study showed a positive impact of privacy on success of electronic customer relationship management. It indicates that privacy provided by insurance company leads to success of electronic customer relationship management systems. Similarly, the study showed a positive impact of reliability on success of electronic customer relationship management systems. It indicates that higher the reliability of customers towards insurance sectors leads to higher the success of electronic customer relationship management systems. Likewise, the study showed a positive impact of responsiveness on success of electronic customer relationship management systems. It indicates that positive response from the insurance sector regarding the online services leads to higher the success of electronic customer relationship management systems. In addition, the study also showed a positive impact of trust on success of electronic customer relationship management systems. It indicates that higher the trust of customers towards insurance sector leads to higher the success of electronic customer relationship management systems. Further, the study showed a positive impact of consumer satisfaction on success of electronic customer relationship management systems. It indicates that higher the consumer satisfaction, higher would be the success of electronic customer relationship management systems.